2011
DOI: 10.1007/s12028-011-9621-9
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tissue Oxygen-Based Therapy and Outcome After Severe Traumatic Brain Injury: A Systematic Literature Review

Abstract: Observational clinical studies demonstrate that brain hypoxia is associated with poor outcome after severe traumatic brain injury (TBI). In this study, available medical literature was reviewed to examine whether brain tissue oxygen (PbtO2)-based therapy is associated with improved patient outcome after severe TBI. Clinical studies published between 1993 and 2010 that compared PbtO2-based therapy combined with intracranial and cerebral perfusion pressure (ICP/CPP)-based therapy to ICP/CPP-based therapy alone w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(75 citation statements)
references
References 42 publications
0
74
1
Order By: Relevance
“…Studies [26,27] have since confirmed that low PbtO2 of less than 10 for 15 min are associated with worse clinical outcomes and some prospective studies as well as multiple non-randomized studies comparing ICP/CPP-driven protocols versus ICP/CPP and PbtO2-driven protocols, and a pooled analysis of these that included 491 patients suggests that there is a twofold likelihood of better outcomes with the PbtO2 and ICP/CPP-driven protocols [28]. There is still no class 1 evidence, but an ongoing randomized clinical trial in TBI patients will hopefully shed some light on this.…”
Section: Pbto2mentioning
confidence: 96%
“…Studies [26,27] have since confirmed that low PbtO2 of less than 10 for 15 min are associated with worse clinical outcomes and some prospective studies as well as multiple non-randomized studies comparing ICP/CPP-driven protocols versus ICP/CPP and PbtO2-driven protocols, and a pooled analysis of these that included 491 patients suggests that there is a twofold likelihood of better outcomes with the PbtO2 and ICP/CPP-driven protocols [28]. There is still no class 1 evidence, but an ongoing randomized clinical trial in TBI patients will hopefully shed some light on this.…”
Section: Pbto2mentioning
confidence: 96%
“…49 Despite its complicated dependence on multiple physiological factors, brain hypoxia is an independent predictor of poor outcome in brain-injured patients, 38,44,45 and PbtO 2 threshold-based treatment strategies may improve outcomes. 4,41 Monitoring devices for PbtO 2 measure local tissue oxygen tension and may not reflect global brain oxygenation. In addition, probe placement can cause local tissue injury, leading to falsely low measurements.…”
Section: Brain Tissue Oxygen Tensionmentioning
confidence: 99%
“…It has also been emphasized that the surgeon/physician in charge of pbtO2 monitoring must have experience in data interpretation: "It is equally important that the clinician understands relevant aspects of brain oxygen physiology and head trauma pathophysiology to enable correct interpretation of the monitored data and therefore to direct an appropriate therapeutic response that is likely to benefit, not harm, the patient" [348]. Three reviews have underlined the known fact of a lack of a randomized trial to prove the utility of pbtO2 monitoring which, speaking from a strictly scientific point of view, is needed to recommend its unrestricted routine use [200,273,325]. In keeping with this view a recent comprehensive pbtO2 review concludes that the current scientific literature implies that: "...…”
Section: Pbto2 Monitoring Reviews and Critical Appraisalmentioning
confidence: 99%